2021
DOI: 10.3389/fmed.2021.668913
|View full text |Cite
|
Sign up to set email alerts
|

PRAgmatic Clinical Trial Design of Integrative MediCinE (PRACTICE): A Focus Group Series and Systematic Review on Trials of Diabetes and Kidney Disease

Abstract: Background: Pragmatic trials inform clinical decision with better generalizability and can bridge different streams of medicine. This study collated the expectations regarding pragmatic trial design of integrative medicine (IM) for diabetes and kidney diseases among patients and physicians. Dissonance between users' perspective and existing pragmatic trial design was identified. The association between risk of bias and pragmatism of study design was assessed.Method: A 10-group semi-structured focus group inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…Most existing trials assessed single Chinese medicine formulation either (1) in all participants without personalization or (2) in a phenotype-based subset with limited representation of the diabetic CKD population. 10,16 Assessing Chinese medicine as a program intervention 20 better mimics clinical practice. Phenotype-stratified randomization facilitates the analysis of effectiveness at both the program level (in the whole diabetic CKD population) and formulation level (in each phenotype subgroup) without excluding patients by phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Most existing trials assessed single Chinese medicine formulation either (1) in all participants without personalization or (2) in a phenotype-based subset with limited representation of the diabetic CKD population. 10,16 Assessing Chinese medicine as a program intervention 20 better mimics clinical practice. Phenotype-stratified randomization facilitates the analysis of effectiveness at both the program level (in the whole diabetic CKD population) and formulation level (in each phenotype subgroup) without excluding patients by phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Along with the recruitment domain for which 31.2% of the studies were left blank, the rate of the score 'blank' was 84.9% and relatively higher than other domains, and this tendency was shown in a previous study assessing integrative medicine research. [22] In the real-world setting, methods such as sending messages or making phone calls for upcoming appointments may plausibly be used; however, attendance would not be compulsorily forced. Future PATs should explore this issue in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…Free energy was used to estimate the strength of bonding for better estimating the binding affinity instead of using root-mean-square deviation from geometric assessment ( Cournia et al, 2017 ; Mobley and Gilson, 2017 ). Subsequent validation from clinical samples screening the biomarkers of key mechanisms would serve better to evaluate the whole-system effect and the relative involvement of different mechanisms of the formulations in real clinical settings ( Chan et al, 2021c ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous registry studies showed that individualized Chinese medicine (CM) treatment was associated with slower decline of kidney function and reduced risk of end-stage kidney failure and mortality among patients with CKD and diabetes ( Hsieh et al, 2014 ; Lin et al, 2015 ; Huang et al, 2018 ; Chan et al, 2022 ). CM formulations are prescribed based on symptom-based diagnosis ( Chan et al, 2020a ; Chan et al, 2020b ; Chan et al, 2021a ; Chan et al, 2021b ; Chan et al, 2021c ; Shu et al, 2021 ), which predicts renal function decline independent of blood pressure, blood glucose, lipids, and urine albumin control ( Chan et al, 2021b ). The CM used in these cohorts mostly contained a classical CM formulation, namely, Rehmannia-6 complex (R-6, Liu-wei-di-huang-wan) with variations according to the symptom-based diagnosis.…”
Section: Introductionmentioning
confidence: 99%